2017
DOI: 10.1073/pnas.1713308114
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in associative memory among older adults explained by hippocampal subfield structure and function

Abstract: Older adults experience impairments in episodic memory, ranging from mild to clinically significant. Given the critical role of the medial temporal lobe (MTL) in episodic memory, age-related changes in MTL structure and function may partially account for individual differences in memory. Using ultra-high-field 7T structural MRI and high-resolution 3T functional MRI (hr-fMRI), we evaluated MTL subfield thickness and function in older adults representing a spectrum of cognitive health. Participants performed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 71 publications
5
51
1
Order By: Relevance
“…Four studies reported age-invariant, positive relationships between the magnitude of hippocampal encoding (de Chastelaine et al, 2016a) or retrieval (Daselaar et al, 2006;de Chastelaine et al, 2016b; effects and memory performance. By contrast, other studies examining such relationships in samples of older adults have reported negative relationships for encoding- (Miller at al., 2008) or retrieval-related activity (Carr et al, 2017), or a null relationship Duarte, 2011, 2016). In a similar vein, Daselaar et al (2015) reported a negative relationship between hippocampal recollection effects and a composite index of memory function derived from a neuropsychological test battery.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported age-invariant, positive relationships between the magnitude of hippocampal encoding (de Chastelaine et al, 2016a) or retrieval (Daselaar et al, 2006;de Chastelaine et al, 2016b; effects and memory performance. By contrast, other studies examining such relationships in samples of older adults have reported negative relationships for encoding- (Miller at al., 2008) or retrieval-related activity (Carr et al, 2017), or a null relationship Duarte, 2011, 2016). In a similar vein, Daselaar et al (2015) reported a negative relationship between hippocampal recollection effects and a composite index of memory function derived from a neuropsychological test battery.…”
Section: Introductionmentioning
confidence: 99%
“…How do aHC and pHC changes relate to episodic memory performance? Volumetric studies have yielded mixed results (Van Petten, 2004), but there are indications in favor of longitudinal compared to cross-sectional relationships (Fjell, McEvoy, et al, 2013; Gorbach et al, 2017; Tamnes et al, 2014), and that correlations may be stronger in certain hippocampal regions (Carr et al, 2017; Daugherty et al, 2017; DeMaster et al, 2014; Hackert et al, 2002; Nordin, Herlitz, Larsson, & Soderlund, 2017; Valdes Hernandez et al, 2017), reflecting specific parts of the memory process (Nadel et al, 2012; Poppenk et al, 2013; Poppenk & Moscovitch, 2011). In addition, relationships may be different in development vs. adulthood and aging (DeMaster et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More specific to underlying brain networks in aging, there is considerable evidence that the behaviors dependent on the hippocampus undergo substantial changes in aging (Samson et al, 2013). Pattern of hippocampal connections with cortical areas (whether directly or indirectly) is also altered (For a detailed overview see Eichenbaum, 2017) which has been linked to changes in cognitive functions in late adulthood (Carr et al, 2017;Fjell et al, 2016;Salami et al, 2014).…”
Section: Age-related Changes In the Structure And Function Of The Hipmentioning
confidence: 99%